Inventor’s Legal Liability upon the Invention of Artificial Intelligence in Indonesia - Deslaely Putranti; Kurnia Dewi Anggraeny (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
The pace of technological development can no longer be restrained until the emergence of artificial intelligence (AI), which later turns out to negatively impact its application. AI is a computer system program created by humans. On the one hand, the invention of AI makes human work easier. On the other hand, it is also noticeable that there are several criminal cases